STAND FOR TEST HYDRAULIC MACHINES WITH RECUPERATION OF THE ENERGY - A.T. RYBAK; A.V. SERDYUKOV (Advanced Engineering Research, 2009)
The principle scheme of the stand is оffered for test the hydraulic machines with economy of the energy. Happens to its mathematical model and information about its preliminary analysis.